How personal values shape job seeker preference: A policy capturing study. - Carol L Hicklenton (Public Library of Science (PLoS), 2021)
Does the "ideal" organization exist? Or do different workplace attributes attract different people? And if so, what attributes attract what types of employees? This study combines person-organization fit theory and a policy capturing methodology to determine (a) which attributes are the strongest predictors of perceived organization attractiveness in a sample of Australian job seekers, and (b) whether the magnitude of these predictive effects varies as a function of job seekers' personal values. The design of this study is a randomized experiment of Australian job seekers who responded to an online survey invitation. Each of the 400 respondents received a random subset of 8 of 64 possible descriptions of organizations. Each description presented an organization that scored either high or low on six attributes based on the Employer Attractiveness Scale: economic, development, interest, social, application, and environmental value. Multi-level modelling revealed that all six attributes positively predicted job seekers' ratings of organization attractiveness, with the three strongest predictors being social, environmental, and application value. Moderation analyses revealed that participants with strong self-transcendent or weak self-enhancement values were most sensitive to the absence of social, environmental, and application value in workplaces, down-rating organizations that scored low on these attributes. Our results demonstrate how job seekers' personal values shape preferences for different types of workplaces. Organizations may be able to improve recruitment outcomes by matching working conditions to the personal values of workers they hope to employ.